(untitled) (Research, Society and Development, 2021)
The present work aims to add liquid soap to the concrete matrix during manufacture, in order to investigate the consistency reduction capacity provided by this compound in comparison to the concrete produced with the commercial plasticizer additive, sodium acetate and the reference concrete, that is, without additives. After determining the concrete mix, seven productions took place, with the concrete dosed in 1% and 2% with liquid soap, the concrete dosed in 1% and 2% with commercial plasticizer additive, the concrete dosed in 1% and 2% of sodium acetate and finally the reference matrix, without additions. The results were obtained through the slump tests with the cone trunk, evaluating therefore the reduction of the consistency through the measurement of the deformation of the matrix. The matrix dosed with liquid soap produced abatement values ​​higher than the reference concrete with the two dosage percentages. In relation to the concrete produced with a commercial plasticizer additive, the matrix dosed with liquid soap at 1% generated an upper and lower abatement value for 2%. The matrix made with sodium acetate developed high rigidity, with two percentages of dosage, presenting an absence of mobility, therefore, without abatement. Analyzing the results, it is understood that the use of liquid soap, easy to prepare, low cost and ecologically sustainable, developed a reduction in the consistency of the concrete, therefore, assuming characteristics of a possible consistency reducing agent, analogous to the commercial plasticizer additive.